AN LC-ESI-MS/MS METHOD DEVELOPMENT AND VALIDATION FOR THE QUANTIFICATION OF INFIGRATINIB IN BIOLOGICAL MATRICES - SUNKARA, PHANI KUMAR; CHAGANTY, SREEDHARA; RAMAKRISHNA, K. (International Journal of Applied Pharmaceutics, 2024)
Objective: The study was aimed to develop a precise and simple liquid chromatographic electrospray ionization tandem mass spectrometric (LC-ESI-MSMS) technique is essential for the quantification of Infigratinib in biological matrices. Methods: Chromatographic resolution was attained with PhenominexC18 (50 mm×2.6 mm, 3 µm) stationary column and a mobile solvent composition of 0.1% HCOOH, methyl alcohol and acetonitrile in the proportion of 10:10:80. Chromatograms were resolved by an isocratic separation with a flowing rate of 0.50 ml/min at 40 °C. Results: Quantitation was executed by monitoring the transitions of m/z. 560.19/189.13 for Infigratinib and 494.5→394.5 for Imatinib internal standard in multiple reaction monitoring. The standard curve regression line was y = 0.0016x+0.0062 and the correction coefficient (r2) was 0.9994. The % CV outcomes for matrix effect at Lower-QC and Higher-QC were 4.95% and 3.61% respectively. The percentage average recoveries for Infigratinib in Higher-QC (900ng/ml), MQC (600ng/ml) and Lower-QC (3ng/ml) were 93.27%, 94.69% and 97.24% respectively. The intra and interday precisions of analytical procedure was estimated by assessing the %CV outcomes and were in between 1.88 to 5.93% for the QC samples. Conclusion: The developed procedure can be useful for the assessment of Infigratinib in biological matrices in quality control, forensic and bioavailability studies.